The Effect Of Flour Variations On The Organoleptic Properties Of Betung Bamboo Chips (Dendrocalamus asper) - syariatul rofiah; Riyadlul Akbar; Mohammad Nurul Hidayatullah (TAPE : Jurnal Teknologi Hasil Pertanian, 2025)
Bamboo shoots (Dendrocalamus asper) are young bamboo shoots that appear on the surface of the base of bamboo clumps and are usually covered by fine hairs or gugut. Bamboo shoots have various good nutritional contents so they can be processed into chips. Bamboo shoot chips (Dendrocalamus asper) are food made from bamboo shoots that are thinly sliced ​​then boiled, drained, mixed with a variety of flour that has been added with flavorings and then fried. The purpose of this study was to determine the effect of organoleptic properties of bamboo shoot chips with variations in flour. The research method used ANOVA with 4 treatments, namely: P0: 60gr bamboo shoots + Without flour, P1: 60gr bamboo shoots + 60gr wheat, P2: 60gr bamboo shoots + 60gr rice flour and P3: 60gr bamboo shoots + 60gr tapioca flour. Data analysis in the organoleptic test used One Way Anova and Duncan's further test. The results of the One Way Anova analysis test showed a significance value of the texture aspect of p < 0.05 so that it can be concluded that there is a real difference or there is an influence on the texture of bamboo shoot chips and can be further tested with the Duncan test which produces P0, P3, P1, and P2 there is a real difference or there is an influence on the texture of bamboo shoot chips.